Exploring Meaning, Motivation, and Nationalism among Indonesian Gen Z in the #KaburAjaDulu Digital Campaign: A Phenomenological Study - Nabilla Anasty Fahzaria; Andalusia Neneng Permatasari; Raditya Pratama Putra (Universitas Ahmad Dahlan, 2026)
The viral #KaburAjaDulu digital campaign on social media has emerged as an expression of public frustration with economic inequality, limited opportunities, and social injustice in Indonesia, particularly among Generation Z as the dominant group of internet users. This phenomenon raises questions about how young people interpret nationalism in the context of digital discourse and socio-political dissatisfaction. This study examines how Indonesian Generation Z interpret the #KaburAjaDulu digital campaign, the motivations behind their responses, and how the campaign shapes their understanding of nationalism. Using Alfred Schutz's phenomenological approach, the study employed semi-structured interviews with 15 Generation Z social media users who actively followed the campaign. The findings reveal that the campaign is not merely perceived as an invitation to leave the country, but as a digital expression of collective frustration, a symbolic critique of structural limitations, and a way of coping with uncertain futures. Participants' motivations range from pragmatic aspirations for better opportunities abroad to expressions of satire and protest in digital spaces. Their views on nationalism appear increasingly critical and conditional, reflecting a shift from conventional patriotism toward a more reflective sense of belonging. These findings highlight digital campaigns as spaces for youth political expression and identity negotiation, underscoring the need for policy responses that address Generation Z's socio-economic concerns.